2011
DOI: 10.1080/15295192.2011.585554
|View full text |Cite
|
Sign up to set email alerts
|

Attributions and Attitudes of Mothers and Fathers in Colombia

Abstract: SYNOPSIS Objective The present study examined mean level similarities and differences as well as correlations between mothers’ and fathers’ attributions regarding successes and failures in caregiving situations and progressive versus authoritarian attitudes. Design Interviews were conducted with both mothers and fathers in 108 Colombian families. Results Fathers reported higher uncontrollable success attributions and higher authoritarian attitudes than did mothers, whereas mothers reported higher modernit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…This variability is consistent with previous research that has shown cultural normativeness of corporal punishment to moderate the relation between corporal punishment and children’s adjustment (Gershoff et al, 2010; Lansford et al, 2005). In the more authoritarian groups in this study, parents have been found to value children’s obedience and conformity to parents’ directives (e.g., Alampay & Jocson, 2011; Al-Hassan & Takash, 2011; Bornstein et al, 2011; Di Giunta et al, 2011; Oburu, 2011). Thus, in the more authoritarian contexts, corporal punishment may have been part of a broader pattern of culturally endorsed no-nonsense parenting, although the overall effect of corporal punishment was still adverse.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This variability is consistent with previous research that has shown cultural normativeness of corporal punishment to moderate the relation between corporal punishment and children’s adjustment (Gershoff et al, 2010; Lansford et al, 2005). In the more authoritarian groups in this study, parents have been found to value children’s obedience and conformity to parents’ directives (e.g., Alampay & Jocson, 2011; Al-Hassan & Takash, 2011; Bornstein et al, 2011; Di Giunta et al, 2011; Oburu, 2011). Thus, in the more authoritarian contexts, corporal punishment may have been part of a broader pattern of culturally endorsed no-nonsense parenting, although the overall effect of corporal punishment was still adverse.…”
Section: Discussionmentioning
confidence: 72%
“…Of the countries included in the present study, there were conceptual as well as empirical reasons for grouping Colombia (Di Giunta, Uribe Tirado, & Márquez, 2011), Jordan (Al-Hassan & Takash, 2011), Kenya (Oburu, 2011), the Philippines (Alampay & Jocson, 2011), and the African Americans from the United States (Lansford, Bornstein et al, 2011) as contexts with more authoritarian attitudes about parenting. Parents in these groups tend to emphasize the hierarchical nature of parent-child relationships and the importance of children’s obedience and compliance (Bornstein, Putnick, & Lansford, 2011).…”
Section: The Importance Of An International Perspectivementioning
confidence: 99%
“…These findings indicate that the relation between adolescent communication efforts and internalizing problems in Jordanian and Colombian adolescents was negative and intertwined such that adolescents who experienced internalizing problems disclosed less over time, while their secrecy toward parents resulted in more internalizing problems over time. In both Jordanian and Colombian culture, respect and guidance (Oweis et al 2012) as well as loyalty and attachment between family members (Di Giunta et al 2011) are especially strongly valued. Consequently, non-normative lack of communication between parents and adolescents in these cultures might be especially deleterious to both parent-adolescent communication and adolescent internalizing symptoms, given the central role family relationships play in both Jordan and Colombia.…”
Section: Are the Links Between Parent-adolescent Communication Effortmentioning
confidence: 99%
“…Dentro de la corriente principal de estudios de prácticas parentales asociadas al aprendizaje escolar de estudiantes que cursan la enseñanza básica, destacan aquellos que se desarrollan desde el modelo de estilos educativos parentales de Baumrind (1971) -posteriormente ajustado por Maccoby y Martin, 1983-(Dehyadegary, Yaacob, Juhari & Talib, 2012Di Giunta, Uribe Tirado & Araque Márquez, 2011;Domenech Rodríguez, Donovick & Crowley, 2009;Drummond & Stipek, 2004;Seginer, 2006), actualmente desarrollado por Cumsille, Martínez, Rodríguez y Darling (2014) en Chile, quienes contribuyen, además, con la validación de la Escala Parental Breve (EPB) para la medición de prácticas parentales en familias con hijos adolescentes. El estilo educativo se define aquí como "(…) el conjunto de actitudes que los padres comunican a sus hijos a través de las interacciones con ellos y que crean un clima en el cual los comportamientos de los padres son interpretados por los niños y adolescentes" (Cumsille et al, 2014, p. 1).…”
Section: Prácticas Parentales Y Las Diferencias En Resultados Escolarunclassified